2015
DOI: 10.4103/0366-6999.156782
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Lower-limb Deep Venous Thrombosis in Old Patients after Knee Arthroplasty

Abstract: Background:Deep venous thrombosis (DVT) is a common complication of arthroplasty in old patients. We analyzed risk factors for lower-limb DVT after arthroplasty in patients aged over 70 years to determine controllable risk factors.Methods:This was a retrospective study of 1,025 patients aged >70 years treated with knee arthroplasty at our hospital between January 2009 and December 2013. Of 1,025 patients, 175 had postoperative lower-limb DVT. We compared medical history, body mass index (BMI), ambulatory blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 24 publications
1
34
2
Order By: Relevance
“…In our study, we had the similar conclusion and also found in multivariate analysis that age, malignant tumor, hypertension were independent risk factors of DVT. Patients with older age are often associated with vascular sclerosis, high blood viscosity and poor venous valve function, this lead to a high rate of lower limb DVT when combined with reduced activity postoperatively 13. The influence of malignant tumor and hypertention on DVT was also confirmed by some clinical studies 14-16.…”
Section: Discussionmentioning
confidence: 91%
“…In our study, we had the similar conclusion and also found in multivariate analysis that age, malignant tumor, hypertension were independent risk factors of DVT. Patients with older age are often associated with vascular sclerosis, high blood viscosity and poor venous valve function, this lead to a high rate of lower limb DVT when combined with reduced activity postoperatively 13. The influence of malignant tumor and hypertention on DVT was also confirmed by some clinical studies 14-16.…”
Section: Discussionmentioning
confidence: 91%
“…After screening title/abstract and full‐text information, 728 were excluded because of duplicated publications, and 1610 were excluded because the data they provided was not available or unrelated to our topic. Finally, 23 articles that met the inclusion criteria were included in this meta‐analysis . The flow chart of the search strategy is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported data on the incidence of VTE . The pooled estimates, using a random‐effect model, indicated that the incidence of VTE in patients who underwent surgery for fractures below the hip was 21% (95%CI: 17%, 24%; P = 0·000) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Kang et al [17] DVT was detected by B-mode ultrasonography performed 7 days after TKR in 175/1025 patents aged >75 years. Diabetes (P = 0.014), high body mass index (BMI) (P = 0.003) and hyperomocysteinemia (P < 0.001) were significantly more frequent in the thrombus group.…”
Section: Pathophysiologymentioning
confidence: 99%